2018
DOI: 10.1039/c8cc02048e
|View full text |Cite
|
Sign up to set email alerts
|

Finding a receptor design for selective recognition of perrhenate and pertechnetate: hydrogen vs. halogen bonding

Abstract: Receptors bearing hydrogen and halogen bond donors for recognition of perrhenate and pertechnetate were designed and studied. Acyclic hosts with N-H and C-H binding sites showed the best selectivity for TcO4- and ReO4- over spherical and more basic tetrahedral anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…As inferred from our previous studies [8], the acylation of p-xylylenediamine leads to the formation of two amide groups, which serve as hydrogen bond donor sites for the coordination of two oxygen atoms of perrhenate or pertechnetate anions. The distance between the amide groups of 7 Å is optimal to achieve binding complementarity between two oxygen atoms of the perrhenate anion and NH-binding sites.…”
Section: Design and Synthesismentioning
confidence: 68%
See 3 more Smart Citations
“…As inferred from our previous studies [8], the acylation of p-xylylenediamine leads to the formation of two amide groups, which serve as hydrogen bond donor sites for the coordination of two oxygen atoms of perrhenate or pertechnetate anions. The distance between the amide groups of 7 Å is optimal to achieve binding complementarity between two oxygen atoms of the perrhenate anion and NH-binding sites.…”
Section: Design and Synthesismentioning
confidence: 68%
“…The design of artificial anion receptors is a challenge in supramolecular chemistry that has received great attention in recent years [1][2][3][4][5][6], moving from being an entirely fundamental area of supramolecular chemistry to a range of applications. Perrhenate (ReO 4 − ) and pertechnetate (TcO 4 − ) are considered to be the anions that are among the most "difficult to bind" due to their relatively large size and low charge density [7,8]. These anions are available from 99 Mo/ 99m Tc and 188 W/ 188 Re generators and are widely used in nuclear medicine as a part of diagnostic imaging tools and therapeutic devices [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, ReO 4 À does not react with HCl while TcO 4 À is actively reduced (German et al, 2002). We found that in the presence of Mg 2+ , the ReO 4 À being distorted according to (Khrustalev, 2000;Ravi et al, 2018) attacks the HCl, forming Cl 2 that is readily reacted with water to form HOCl. In the air and in low acidic HClÁH 2 O solution, the Re is then oxidized back to Re VII .…”
Section: Synthesis and Crystallizationmentioning
confidence: 91%